2020
DOI: 10.1192/j.eurpsy.2019.14
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of stigma in a sample of mental health professionals: Network and moderator analysis on gender, years of experience, personality traits, and levels of burnout

Abstract: Background. Stigma is one of the most important barriers to help-seeking and to personal recovery for people suffering from mental disorders. Stigmatizing attitudes are present among mental health professionals with negative effects on the quality of health care. Methods. Network and moderator analysis were used to identify what path determines stigma, considering demographic and professional variables, personality traits, and burnout dimensions in a sample of mental health professionals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 75 publications
3
27
1
Order By: Relevance
“…In our sample, high emotional exhaustion and depersonalization were related to stigmatizing attitudes towards people with mental illness, while a high level of personal accomplishment was associated with more favorable attitudes. The results of the present study are consistent with those of recent field research showing that emotional exhaustion, depersonalization, and low personal accomplishment predict the stigmatizing attitudes of MHPs towards people with mental disorders (Holmqvist & Jeanneau, 2006 ; Solmi et al, 2020 ; Zaninotto et al, 2018 ). In their study, Holmqvist and Jeanneau ( 2006 ) showed that MHPs’ burnout levels, measured in terms of tedium, emotional exhaustion, depersonalization, and personal accomplishment, were associated with MHPs’ feelings towards service users with a mental illness diagnosis.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our sample, high emotional exhaustion and depersonalization were related to stigmatizing attitudes towards people with mental illness, while a high level of personal accomplishment was associated with more favorable attitudes. The results of the present study are consistent with those of recent field research showing that emotional exhaustion, depersonalization, and low personal accomplishment predict the stigmatizing attitudes of MHPs towards people with mental disorders (Holmqvist & Jeanneau, 2006 ; Solmi et al, 2020 ; Zaninotto et al, 2018 ). In their study, Holmqvist and Jeanneau ( 2006 ) showed that MHPs’ burnout levels, measured in terms of tedium, emotional exhaustion, depersonalization, and personal accomplishment, were associated with MHPs’ feelings towards service users with a mental illness diagnosis.…”
Section: Discussionsupporting
confidence: 91%
“…Along with individual factors contributing to MHPs attitudes towards mental illness, such as empathy levels (Economou et al, 2019 ) and personality traits (Solmi et al, 2020 ), work environment and practice-related factors may also play a significant role in service provision. Specifically, practice-related factors such as the length of practice (Hsiao et al, 2015 ; Stuber et al, 2014 ), work setting (Hsiao et al, 2015 ; Linden & Kavanagh, 2011 ), and the type of mental health profession (Lebowitz & Ahn, 2014 ; Reavley et al, 2013 ; Smith et al, 2017 ) appear to be associated with MHPs stigmatizing attitudes towards service users.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, a more differentiated understanding on the diverse implications of masculinity for mental health would be essential with regards to future interventions, for which further research that incorporates a critical examination of traditional masculinity is required [45]. Interventions to reduce mental illness stigma in health professionals may need to run a multilevel approach, adjusted to groups of health professionals with varying characteristics of stigmatising attitudes [46,47] personality characteristics and job strain of MHPs [48].…”
Section: Discussionmentioning
confidence: 99%